Evaluating the Influence of Cetane Improver Additives on the Outcomes of a Diesel Engine Characteristics Fueled with Peppermint Oil Diesel Blend - Paneerselvam, Purushothaman; Venkadesan, Gnanamoorthi; Panithasan, Mebin Samuel; Alaganathan, Gurusamy; Wierzbicki, Sławomir; Mikulski, Maciej (MDPI, 2021)
This paper aims to evaluate the impact of cetane improvers on the combustion, performance and emission characteristics of a compression ignition engine fueled with a 20% peppermint bio-oil/diesel blend (P20). It is hypothesized that the low viscosity and boiling point of peppermint oil could improve the atomization characteristics of the fuel. However, the usage of peppermint oil is restricted due to its low cetane index. To improve this, Diethyl Ether (DEE) and Di-tertiary Butyl Peroxide (DTBP) are added to the P20 blend. The tests are performed in a single-cylinder naturally aspirated water-cooled diesel engine and results indicate that NOx emission for P20 + DEE and P20 + DTBP is decreased by 10.4% and 9.8%, respectively, when compared to P20 at full load condition. Among these two cetane improvers, DTBP is more effective in reducing the CO, HC and smoke emission and the performance of the engine was reported to be higher for P20 + DTBP blends.
Keywords: biofuel; combustion; DEE; DTBP; emission; peppermint; fi=Energiatekniikka|en=Energy Technology|